Life in extreme Oceans: Calcareous Nannoplankton adaptations and strategies during Oceanic Anoxic Event 2 - G. Faucher; E. Erba; C. Bottini (International Nannoplankton Association, 2013)
At present about one third of the carbon dioxide (CO2) released in the atmosphere from fossil fuel burning is absorbed by the oceans. The invasion of anthropogenic CO2 into the oceans increases seawater acidity and decreases carbonate ion concentration and carbonate saturation. This dramatic change of the carbonate system can have a huge impact on the marine ecosystem and, in particular, can seriously impair marine calcifiers (e.g. corals, foraminifera, coccolithophores). Coccolithophorid algae are sensitive to ocean acidification and most studies show a strong decline in growth and/or reduction in calcification rate and/or increase in coccolith malformation with increasing CO2 concentration. During the Cretaceous the Earth has already experienced extreme environmental change: the construction of Large Igneous Provinces (LIPs), forming gigantic oceanic plateaus, affected the ecosystem at global scale. LIP volcanism probably triggered global warming and enhanced primary productivity with consequent oxygen consumption and burial of massive amounts of organic matter at global scale: these episodes are known as Oceanic Anoxic Events (OAEs). We investigated calcareous nannoplankton morphological variation through one of the most interesting anoxic event of the Cretaceous, the latest Cenomanian OAE2. This episode of global anoxia is associated with the formation of the Caribbean Plateau (CP) that triggered high release of excess CO2, causing a general global warming. Recent studies of the OAE2 episode have pointed out climatic variability and fluctuations in the atmCO2 concentration. In fact, a cooling episode and CO2 drop in the early phase of OAE2 is connected with a weathering spike, followed by a new increase in CO2 and warming. We investigated OAE2 sections from Sicily, Southern France, England and Colorado. The major result that we observed is a change to tiny-dwarf coccoliths, although of different amplitude, through OAE2: calcareous nannofossil size variations follow the pCO2 fluctuations and record an ...